The Sources of National Translations of the Holy Scripture: English and Ukrainian Context (Linguostylistic Studies, 2017)
The article highlights the specificity of synchronic and diachronic English and Ukrainian translations of the Holy Scripture determined by the difference of their prototexts. The author differentiates several levels of the sources. The sources of the first level include Masoretic Hebrew texts and Greek Septuagint, the list being supplemented with the Dead Sea Scrolls. In their turn Masoretic texts and Septuagint laid the foundation for the Latin (Western) and Byzantine (Eastern) traditions of Bible translations, actualized in the sources of the second level – the Vulgate and the Church-Slavonic translation accordingly. Sources of the third level cover the translations, canonized in a certain lingual culture, i.e. they are authorized by the Church and/or popular among the believers and are frequently quoted in extra-Biblical discourses. In the Anglophone world King James’ Bible (1611) has an undisputably authorized status. It is difficult to single out any unique source of the third level in the Ukrainian tradition, although Russian Synod translation, the first complete Ukrainian Bible (1903) and the translation by I.Ohiienko can be considered as the most obvious samples of it.
Keywords: Masoretic texts; Septuagint; Latin tradition of the Bible translation; Byzantine tradition of the Bible translation; prototext; authorized translation of the Bible